Al-Cu powder oxidation kinetics during heating in air - Korotkikh, Alexander G. (Combustion, explosion, and shock waves)
The use of nanosized metal powders is a promising direction in the development of modern energy compositions due to their high reactivity and intense heat release upon contact with an oxidizer and during combustion. The results of a combined analysis (thermogravimetric analysis and differential scanning calorimetry) of Alex aluminum nanopowders and a Al-Cu compound, obtained via electrical explosion of conductors, are presented at constant heating rates of 2, 4, and 20 degrees C /min in air in a temperature range of 30-1300 degrees C . It is revealed that Alex and Al-Cu nanopowders are intensely oxidized when heated in air to a temperature of 600 degrees C due to the oxidizer diffusion through the porous oxide layer Al2O3 and the possible formation of open surfaces of an active metal during a phase change in the crystal lattice of the metal oxide. The Friedman and Kissinger-Akahira-Sunose methods were used to obtain dependences between the activation oxidation energy on the degree of conversion (oxidation) of nanosized metal powders. It is shown that the activation energy of Alex and Al-Cu nanopowders depends on the degree of conversion (oxidation stages) and lies in ranges of 78-307 and 99-430 kJ/mol, respectively.